Dimensions of human existence in the story of Adam; A study on the phenomenon of Quranic narration. - DR.Tahseen Hassan Jassim; Raghad Thamer Ezzat (Journal of College of Education, 2024)
What gives interpretation great effectiveness is to study a text with complex connotations, saturated with symbolism, and with a method that allows for free perceptions that appear to the consciousness. There is no more abundant meaning than the Qur’anic text, nor more radiant with symbolism than its stories that appear in different contexts of its noble verses, and perhaps the most important of them is the story “Adam,” which tells us the story of the beginning of creation, has been read from various perspectives and with different approaches, emerging from its vision of the identity of the Qur’anic story. The research dealt with the most important existential dimensions by which man was unique among all creatures, and his existence was shaped by a specificity with which he was separated from nature, of which he was a unified part. In its great system, the distinctive features of these concepts are encoded in the Qur’anic narrative of the story of “Adam” and are explored by the tools of the phenomenological approach that allow freedom of reading for the narrative consciousness that embedded the existential dimensions in a narrative genre, whether real or imagined, that story that retained its formal structure, symbols and references, in All the holy books and ancient myths, with slight differences in their details, and the research touched upon important semantic references, appeared to be a structure with interconnected elements in the formation of human life, with its intrinsic privacy, and despite transcending the totality of those existential dimensions, and paying attention to what the light did not focus on in This story, and some references to these dimensions may be consistent with much of what has been approved by modern philosophies and cultural studies, despite the great gap between what those philosophies call for and what those sacred texts believe in. Finding a relationship between them makes them a new duality, intersecting as much as they diverge. It is Intense symbolism about what difference establishes as the most important pillars of the multiplicity of beings and concepts
Keywords: Quranic stories, existential dimensions, the story of Adam, narrative, symbol